2022
DOI: 10.1097/apo.0000000000000548
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Massive Open Online Course (MOOC) in Ophthalmic Skills Training for Medical Students: Outcomes and Perspectives

Abstract: Purpose: To integrate a massive open online course (MOOC) into conventional clinical ophthalmology teaching and investigate its impact on the skills of medical students. Methods: This was a nonrandomized, prospective, and comparative study. Seventy-six medical students were assigned to 2 groups before their clinical teaching. Some were asked to follow a MOOC for slitlamp microscope examination but used textbook for preview of visual acuity test (SLMM group, n=39), while others were required to take a MOOC fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Theoretically the integration of multiple teaching methods can make up the shortcomings of any one teaching method, and will have better effect. Such as MOOC and Bite-Sized Teaching were reported that may be promising instructional strategy in medical education [ 9 , 17 , 18 ]. Since flipped classroom requires students to self-study the learning contents in advance, the MOOC and Bite-Sized Teaching are ideally applicable to this kind of demand, which can be accessed through the Internet to facilitate students’ self-study and online self-management .…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically the integration of multiple teaching methods can make up the shortcomings of any one teaching method, and will have better effect. Such as MOOC and Bite-Sized Teaching were reported that may be promising instructional strategy in medical education [ 9 , 17 , 18 ]. Since flipped classroom requires students to self-study the learning contents in advance, the MOOC and Bite-Sized Teaching are ideally applicable to this kind of demand, which can be accessed through the Internet to facilitate students’ self-study and online self-management .…”
Section: Discussionmentioning
confidence: 99%